Line balancing problem with multi-manned workstations and resource constraints: The case of electronics waste disassembly - Yin-Yann Chen; Pourya Pourhejazy; Tzu-Ning Liu (Cleaner Logistics and Supply Chain)
The increasing public awareness of environmental protection and the scarcity of rare earth elements have made closed-loop supply chains a necessity in many sectors. In particular, recycling components and parts from end-of-life consumer electronics have drawn the attention of both academics and practitioners. Disassembly line balancing improves the cost efficiency of recycling operations and hence helps waste management businesses that operate on very narrow profit margins. This study proposes a new mathematical formulation and hybrid metaheuristics to solve the Disassembly Line Balancing Problem (DLBP) considering multi-manned workstations and resource constraints. The transformed AND/OR graph is used for prioritizing disassembly tasks in the modeling process. The method is applied for optimizing a real-world case of laptop disassembly to showcase the usefulness of the proposed approach. The performance of the developed metaheuristics is evaluated for minimizing the number of workstations, operators, and machines involved in the disassembly operations. Further, the results are analyzed through sensitivity analysis. This study is concluded by providing practical insights and suggestions for the future development of DLBPs.